2018
DOI: 10.1155/2018/1736959
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationship between Gastric Emptying and Plasma Glucose Control in Normoglycemic Individuals and Diabetic Patients

Abstract: Gastric emptying and glycemic control pathways are closely interrelated processes. Gastric chyme is transferred into the duodenum with velocities depending on its solid or liquid state, as well as on its caloric and nutritional composition. Once nutrients enter the intestine, the secretion of incretins (hormonal products of intestinal cells) is stimulated. Among incretins, glucagon-like peptide-1 (GLP-1) has multiple glycemic-regulatory effects that include delayed gastric emptying, thus triggering a feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 86 publications
1
25
0
Order By: Relevance
“…Slowing gastric emptying allows for efficient digestion and absorption of nutrients, including glucose [ 13 , 36 , 37 ]. In the current study, the acute and chronic isoleucine treatment did not affect gastric emptying in SLD-mice.…”
Section: Discussionmentioning
confidence: 99%
“…Slowing gastric emptying allows for efficient digestion and absorption of nutrients, including glucose [ 13 , 36 , 37 ]. In the current study, the acute and chronic isoleucine treatment did not affect gastric emptying in SLD-mice.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, gastric emptying was thought to be decreased in diabetic patients and they were excluded from trials investigating preoperative carbohydrate loading for aspiration concerns. As a matter of fact, gastric emptying might be accelerated in diabetic patients (Gustafsson, et al, 2008;Mihai, et al, 2018). Studies reported that rapid gastric emptying occurred in those early type 2 diabetic patients (Schwartz, et al, 1996;Phillips, et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Increased dietary fibre intake [38] or the addition of guar gum to food [39] have been demonstrated to moderately slow gastric emptying and to reduce postprandial glucose in patients with T2D. As well as improving β-cell glucose sensitivity, both GLP1 and GLP1 receptor agonists (GLP1-RA) slow gastric emptying [40]. Amylin and its synthetic analogue, pramlintide, also reduce gastric emptying while improving glycaemia [41].…”
Section: Discussionmentioning
confidence: 99%